Anti‐striational antibodies: Expanding their clinical significance. Issue 4 (22nd September 2020) - Suzuki, Shigeaki; Nagane, Yuriko; Uzawa, Akiyuki; Imai, Tomihiro; Murai, Hiroyuki; Nakahara, Jin; Utsugisawa, Kimiaki
Abstract: Anti‐striational antibodies (StrAbs) have been described as serum immunoglobulins that react with cross‐striations of skeletal muscle in patients with myasthenia gravis (MG). StrAbs were expected to be useful biomarkers of MG; however, because of their low specificity, the diagnostic utility of StrAbs has been limited. The main autoantigens of StrAbs include titin, ryanodine receptor and Kv1.4. MG patients with StrAbs tend to suffer from bulbar symptoms and myasthenic crisis. The most remarkable finding regarding the clinical significance of StrAbs is their association with myositis concomitant with MG. Myocarditis is a lethal complication in MG patients, but it is treatable by immunotherapy. Patients with myocarditis usually show rapid deterioration, with serious arrhythmias and severe heart failure. As myocarditis often develops in patients with myositis accompanied by MG, MG with myositis and/or myocarditis is an important subset of patients. MG is one of the immune‐related adverse events associated with immune checkpoint inhibitors. MG with myositis and/or myocarditis is an infrequent subset of patients in the usual clinical settings; however, it is more common in patients with immune‐related adverse events. Anti‐titin and anti‐Kv1.4 antibodies were preferentially detected in patients with MG with myositis and/or myocarditis, and in patients with late‐onset and thymoma‐associated MG. The detection of StrAbs provides more specific and useful clinical information for the classification and management of MG patients, and identifies diagnostic biomarkers of serious immune‐related adverse events in cancer patients treated with immune checkpoint inhibitors. Abstract : The most remarkable finding regarding the clinical significance of anti‐strational antibodies is their association with myositis concomitant with myasthenia gravis. The detection of anti‐striational antibodies provides more specific and useful clinical information for the classification and management of myasthenia gravis patients, and identifies diagnostic biomarkers of serious immune‐related adverse events in cancer patients treated with immune checkpoint inhibitors.